2005
DOI: 10.1128/jvi.79.14.8904-8908.2005
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Scrapie Induced by Repeated Injections of Subinfectious Prion Doses

Abstract: To clarify the mechanisms leading to the development of Creutzfeldt-Jakob disease in some recipients of pituitary-derived human growth hormone (hGH), we investigated the effects of repeated injections of low prion doses in mice. The injections were performed, as in hGH-treated children, by a peripheral route at short intervals and for an extended period. Twelve groups of 24 mice were intraperitoneally inoculated one, two, or five times per week for 200 days with 2 ؋ 10 ؊5 to 2 ؋ 10 ؊8 dilutions of brain homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…4 to 6 and Tables 1 to 3). Perhaps exposure to repeated low prion doses in nature may in turn lead to more consistent prion shedding by animals so infected, as has previously been inferred for subinfectious doses of scrapie (35), although substantially more data would be needed to support this extrapolation. Additional information is needed to assess the infectivity of excreta deposited in the environment; however, prion shedding of this magnitude in a free-ranging species would seem to pose a substantial challenge to eradication of CWD.…”
Section: Discussionmentioning
confidence: 86%
“…4 to 6 and Tables 1 to 3). Perhaps exposure to repeated low prion doses in nature may in turn lead to more consistent prion shedding by animals so infected, as has previously been inferred for subinfectious doses of scrapie (35), although substantially more data would be needed to support this extrapolation. Additional information is needed to assess the infectivity of excreta deposited in the environment; however, prion shedding of this magnitude in a free-ranging species would seem to pose a substantial challenge to eradication of CWD.…”
Section: Discussionmentioning
confidence: 86%
“…Whereas oral transmission of rodent-adapted scrapie prions is known to be ≈5 orders of magnitude less efficient than transmission by intracerebral inoculation (14,15), the relative efficiency of oral CWD prion transmission is unknown. Multiple exposures to low levels of CWD prions in the environment (16,17), as well as increased infectivity when prions are bound to soil minerals (18), are factors that may influence transmission.…”
Section: Implications For Horizontal Cwd Transmission and Human Exposurementioning
confidence: 99%
“…87 100,101 in contrast, a second study found that repeated doses of low infectivity produced much higher incidences of disease than a single challenge with the same cumulative dose. 102 Given the unequivocal data showing that scrapie and CWD prions are secreted at low levels from multiple routes it seems imperative that the effects of repeat exposures to low levels of prion are investigated further. Given the results with scrapie-contaminated milk and CWD-contaminated saliva, it seems very likely that these low levels of prion in different secreta/excreta are capable of transmitting disease upon prolonged exposure, either through direct animal-to-animal contact or through environmental reservoirs of infectivity.…”
Section: Skin As a Potential Source Of Prion Infectivitymentioning
confidence: 99%